2018
DOI: 10.1093/jas/sky203
|View full text |Cite
|
Sign up to set email alerts
|

The effects of leptin on plasma concentrations of prolactin, growth hormone, and melatonin vary depending on the stage of pregnancy in sheep1

Abstract: The effects of hyperleptinemia and leptin resistance during gestation are unclear. Leptin, an important neuroendocrine regulator, has anorexic effects, but its interactions with other metabolic hormones during pregnancy are unclear. We examined potential roles of leptin in regulating prolactin (PRL), GH, and melatonin plasma concentrations during pregnancy in Polish Longwool ewes. Twelve estrus-synchronized ewes carrying twins after mating were randomly assigned to receive i.v. injections of saline or recombin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
(57 reference statements)
1
3
0
Order By: Relevance
“…Our results here demonstrate that leptin inhibits melatonin synthesis in pigs, which is in agreement with the reports in rats and ewes, 10,[35][36][37] but there are few reports about the leptin signaling pathways and the related mechanisms in the pineal gland. The results of the present study detailed the signaling pathway of leptin inhibiting melatonin synthesis in porcine pineal glands and proved that miR-7 is a mediatory molecule of inhibition of melatonin synthesis by leptin in porcine pineal glands.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results here demonstrate that leptin inhibits melatonin synthesis in pigs, which is in agreement with the reports in rats and ewes, 10,[35][36][37] but there are few reports about the leptin signaling pathways and the related mechanisms in the pineal gland. The results of the present study detailed the signaling pathway of leptin inhibiting melatonin synthesis in porcine pineal glands and proved that miR-7 is a mediatory molecule of inhibition of melatonin synthesis by leptin in porcine pineal glands.…”
Section: Discussionsupporting
confidence: 93%
“…It is known that leptin is an important hormone which inhibits melatonin synthesis in the pineal gland, but the mechanisms by which leptin inhibits melatonin synthesis and the interaction between leptin and miR‐7 remained to be clarified. We thus assayed the effects of leptin on miR‐7 and Aanat expression in the cultured porcine pinealocytes and melatonin levels in the culture media.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When different sources of Ca salts of FA (0.39% of the diet) were fed to pregnant ewes, the supplementation with EPA and DHA increased leptin mRNA relative abundance in the SC adipose tissue (Coleman et al, 2018c). The differences observed in results comparing previous studies (Reseland et al, 2001;Coleman et al, 2018c) and the quadratic response observed in this experiment may be due to the interaction of the amounts and types of FA in each experiment (Yang et al, 2016), and the interaction with stage of gestation (Szczesna et al, 2018). The mechanism of how different FA at different concentrations regulate leptin mRNA relative abundance remains unclear.…”
Section: Ewe Performance and Sc Adipose Tissue Mrna Relative Abundancementioning
confidence: 49%